หลักการใช้งานโดยธรรมของบรรณารักษ์ตามมาตรา 34 แห่งพระราชบัญญัติลิขสิทธิ์ พ.ศ. 2537 กรณีดาวน์โหลดข้อมูลบนอินเทอร์เน็ตโดยศึกษาเทียบเคียงกับการทำซ้ำในงานสิ่งพิมพ์ - อุยพาณิชย์, ธนากร (Journal of Information Science Research and Practice, 2013)
บทคัดย่อ กฎหมายลิขสิทธิ์ภายใต้พระราชบัญญัติลิขสิทธิ์ พ.ศ. 2537 กล่าวถึงความหมายของลิขสิทธิ์ งานอนมีลิขสิทธิ์ การละเมิดลิขสิทธิ์ และการใช้งานโดยธรรมของบรรณารักษ์และนักสารนิเทศ หลักการใช้งานโดยธรรมของรรณารักษ์และนักสารนิเทศ ตามพระราชบัญญัติฉบับนี้ มาตรา 34 ได้กำหนดหลักเกณฑ์ในการทำซ้ำงานอันมีลิขสิทธิ์โดยบรรณารักษ์ของห้องสมุด เป็นการกระทำอันชอบด้วยกฎหมายเป็นข้อยกเว้นการละเมิดลิขสิทธิ์ การดาวน์โหลดข้อมูลบนอินเทอร์เน็ตสามารถนำหลักการใช้โดยธรรมของบรรณารักษ์และนักสารนิทเศมาใช้ได้โดยศึกษาเทียบเคียงกับการทำซื้อในงานสิ่งพิมพ์และกรณีศึกษาฐานข้อมูลออนไลน์และหนังสืออิเล็กทรอนิกส์ ค่าสำคัญ : การใช้งานโดยธรรม; บรรณาร้กษ์; นักสารนิเทศ; ลิขสิทธิ์; อินเทอร์เน็ต Abstract Copyright Law of Thailand which issued under the National Act in B.E. 2537 mentions its definition and scope as the work having legal copyright, copyright violation, and fair use of librarians and informationists. The regulated fair use on the 34th section prescribes that the standard of duplicating copyright work by librarians and /or informationists is a legitimate act. This performance is treated as the copyright exemption. The downloading data and information from the international networks (INTERNET) is also justified as the career fair use. This study is aimed to compare the duplicated copyright works by librarians with printed materials downloading via the Internet - online databases and electronics book. Keyword : Fair use; Librarian; Informationists; Copyright; Internet